Integration of safety risk assessment techniques into requirement elicitation - Yeow, E.; Chiam, Y.K. (2014)
Incomplete and incorrect requirements may cause the safety-related software systems to fail to achieve their safety goals. It is crucial to ensure software safety by identifying proper software safety requirements during the requirements elicitation activity. Practitioners apply various Safety Risk Assessment Techniques (SRATs) to identify, analyze and assess safety risk.Nevertheless, there is a lack of guidance on how appropriate SRATs and safety process can be integrated into requirements elicitation activity to bridge the gap between the safety and requirements engineering practices. In this research, we proposed an Integration Framework that integrates safety activities and techniques into existing requirements elicitation activity.